Demographic characteristics and problem areas of U.P. College of Agriculture freshmen - Simpas, Carmencita S. 1939- ([Quezon City s.n.], 1971)
This study presented a survey of the demographic characteristics and problem areas of the 1970 University of the Philippines College of Agriculture freshmen through these instruments: the background information sheet and the money problems checklist. Certain demographic characteristics were tested for significant relationships. Tests for correlation were made among sex, age, regional origin, major areas and
Thesis (M. Ed.)--University of the Philippines.
Keywords: Philippines. University -- College of Agriculture -- Students